Atypical Ductal Hyperplasia on Ultrasonography-Guided Vacuum-Assisted Biopsy of the Breast: Considerations for Further Surgical Excision. Issue 2 (June 2020) - Kim, Ji Hee; Han, Kyunghwa; Kim, Min Jung; Moon, Hee Jung; Yoon, Jung Hyun; Park, Vivian Youngjean; Kim, Eun-Kyung
Abstract : Abstract: The purposes of this study are to evaluate the upgrade rate of atypical ductal hyperplasia (ADH) diagnosed with ultrasonography (US)-guided vacuum-assisted biopsy (VAB) to malignancy and to identify the factors behind the underestimation. We retrospectively reviewed the pathologic results of US-guided VAB of the breast. A total of 50 ADH lesions that were surgically excised or with more than 12 months of follow-up were included. The upgrade rate of ADH was determined by dividing the number of lesions that were proven malignant on surgical excision by the total number of ADH diagnosed on VAB. Clinical, radiologic, procedural, and pathologic variables were analyzed to identify the factors behind the underestimation. The upgrade rate of ADH was found to be 16.0% (8/50 lesions). In univariable and multivariable analyses, the upgrade rates of ADH did not significantly differ among variables. In a subgroup analysis, according to history of breast cancer, the upgrade rates of ADH were significantly lower for lesions of mass than for lesions of nonmass (0% [0/23 lesions] vs 28.6% [4/14 lesions], P = 0.015), and for lesions without calcifications than for lesions with calcifications (0% [0/22 lesions] vs 26.7% [4/15 lesions], P = 0.021) in the negative history subgroup. ADH lesions in masses or without calcifications in patients without a family or personal history of breast cancer were associated with low upgrade rates. Thus, we suggest that ADH with these features can be followed rather than surgically excised after US-guided VAB.